Miniaturised tri-band microstrip patch antenna design for radio and millimetre waves of 5G devices - Dhurgham Abdulridha Jawad Al-Khaffaf; Ihsan A. Alshimaysawe (Institute of Advanced Engineering and Science, 2021)
This research presents an extremely small, cheap and simple structure of multiple bands antenna, where is the proposed design comprise square-slotted a microstrip patch antenna with triple bands of RF and mm-wave for 5G. The conducting material is a perfect electrical conductor on both sides. The antenna is printed on FR-4 lossy with a 3.9 of epsilon. Our tiny antenna has a size of 1.5357 x 1.5357 mm2. First, the design parameters were calculated using formulas and then these were simulated by the CST MWS. The simulation results show the antenna performance at the RF band from 0 to 3.4096 GHz with 3.29 gain, a value of return loss S11 and bandwidth of -13.229644 and 3.4096 GHz. The designed antenna works at the mm-wave band ranges 43.5-64 GHz with 3.49 gain, -42.419084 S11 and 20.252 GHz BW. Our antenna can also operate at the mm-wave from 81-95 GHz with -22.269547 S11, 4.52 gain, and 14.085 GHz BW. The small size and supported bandwidth of the designed antenna is suitable for thin and fast transmission devices.